A mind-reader does not always have deontological moral judgments and prosocial behavior: A developmental perspective - Jian Hao; Yanchun Liu (Frontiers in Psychology, 2016)
The rationalistic theories of morality emphasize that reasoning plays an important role in moral judgments and prosocial behavior. Theory of mind as a reasoning ability in the mental domain has been considered a facilitator of moral development. The present study examined whether theory of mind was consistently positively associated with morality from middle childhood to late adulthood. Two hundred four participants, including 48 elementary school children, 45 adolescents, 62 younger adults and 49 older adults, completed theory of mind, moral judgment and prosocial behavior tasks. Theory of mind was measured with strange stories that tapped into an understanding of lies, white lies, double bluffs, irony and persuasion. Moral judgments were measured with variants of the trolley dilemma. Prosocial behavior was measured through participants’ performance in an interactive situation in which a helping request was made. The results indicated specific rather than similar developmental trajectories of theory of mind, moral judgments and prosocial behavior. There was a quadratic trend in theory of mind, a combination of quadratic and cubic trends in deontological moral judgments and a linear decline in helping behavior. It is thus suggested that theory of mind may not be associated with morality in an unchanging way during development. Further results indicated that theory of mind and deontological moral judgments were negatively correlated for children, adolescents and older adults but positively correlated for younger adults. Theory of mind and helping behavior were positively correlated for children but negatively correlated for adolescents. However, the relationships disappeared in adulthood. In sum, the present study reveals that theory of mind may be a nice tool for its facilitation of deontological moral judgments and prosocial behavior, but it may also be a nasty tool for its blocking of deontological moral judgments and prosocial behavior. Moreover, theory of mind may be a permanent tool for moral judgment development but a temporary tool for prosocial behavior development. Thus, the present study enriches the rationalistic theories of morality from a developmental perspective. Different relationships between theory of mind and morality from middle childhood to late adulthood are discussed.